The Interaction Between lncRNA SNHG6 and hnRNPA1 Contributes to the Growth of Colorectal Cancer by Enhancing Aerobic Glycolysis Through the Regulation of Alternative Splicing of PKM - Lan, Zhixian; Yao, Xiang; Sun, Kangyue; Li, Aimin; Liu, Side; Wang, Xinke (Frontiers in Oncology, 2020)
Background: Small nucleolar RNA host gene 6 (SNHG6) acts as a carcinogenic gene in colorectal cancer (CRC). However, previous studies on the mechanism by which long non-coding RNA (lncRNA) SNHG6 exerts its carcinogenic effect in CRC have not involved the direct interaction between SNHG6 and proteins, which is a very important carcinogenic mechanism of lncRNAs. Hence our study conducted a comprehensive RNA-binding proteins-mass spectrometry (ChIRP-MS) analysis on SNHG6 to further explore its carcinogenic mechanism in CRC. Methods: Proteins that interact with SNHG6 were found using ChIRP-MS analysis, and were used to construct the protein-protein interactive (PPI) network using STRING, while the core module of the PPI network was identified using the MCODE plugin in Cytoscape. Pathway enrichment analyses were performed on proteins and RNAs that were found to be associated with the expression of SNHG6 or which directly interacted with SNHG6 using WebGestalt. Finally, CatRAPID, miRbase and TargetScanHuman were used to identify the sites of interaction between SNHG6, heterogeneous nuclear ribonucleoprotein A1 (hnRNPA1) and pyruvate kinase M (PKM) mRNA. Results: The expression of SNHG6 in CRC was found to be higher than that of normal tissues, and was positively correlated with a poor prognosis (p<0.05). 467 proteins that are able to interact with SNHG6 in CRC cells were identified using ChIRP-MS analysis and were used to create a PPI network, within which, a core module composed of 44 proteins that performed the function of splicing mRNA, including hnRNPA1, was found to be positively correlated with SNHG6 (p<0.05). The results of the pathway enrichment analyses suggested that SNHG6 played an important role in the metabolism of CRC by affecting the expression of PKM and SNHG6. The increase in the ratio of PKM2/PKM1 was proven using quantitative real-time polymerase chain reaction (qRT-PCR) analysis. Further exploration suggested SNHG6 could bind to hnRNPA1 and PKM. Conclusion: SNHG6 was found to be able to target the mRNA of PKM, as well as induce hnRNPA1 to specifically splice PKM mRNA, which increased the proportion of PKM2/PKM1, which may be an important carcinogenic mechanism in CRC that proceeds through the enhancement of aerobic glycolysis in CRC cells.